PTSD symptoms are associated with visual retrieval performance in OEF/OIF/OND veterans. (November 2017) - Aase, Darrin M.; DiGangi, Julia A.; Babione, Joseph M.; Schroth, Christopher; Levy, David M.; Kennedy, Amy E.; Proescher, Eric; Greenstein, Justin E.; Walters, Robert; Passi, Holly; Langenecker, Scott A.; Phan, K. Luan
Abstract: Posttraumatic stress disorder (PTSD) is associated with poorer performance on neuropsychological tests in veterans. However, prior studies have generally compared individuals with PTSD to control groups, often excluding individuals with moderate symptoms. The present study evaluated neuropsychological performance among OEF/OIF/OND veterans as a function of overall PTSD severity, while also exploring potential associations between cognitive performance and PTSD symptom clusters. Using a brief neuropsychological battery, clinical interviews, and self-report instruments, we evaluated neuropsychological and psychiatric functioning in 90 OEF/OIF/OND veterans. When controlling for the effects of premorbid intellectual functioning and combat exposure, higher PTSD severity predicted worse visual retrieval performance, but not attention, verbal retrieval, visual learning, or executive functioning performance. A trend was observed where higher PTSD symptoms predicted worse verbal learning performance. All PTSD symptom clusters were associated with visual retrieval performance within the full sample. Avoidance and numbing symptoms were associated with verbal learning in the full sample. Findings suggest that among OEF/OIF/OND veterans with a range of PTSD symptoms, the assessment of visual memory may have implications for clinical practice. Highlights: PTSD symptoms and neuropsychological performance were measured in 90 veterans. Higher PTSD symptoms predicted worse visual retrieval performance. Visual retrieval was negatively associated with all PTSD subscales. Verbal learning was negatively associated with Avoidance and Numbing symptoms.